Risk factors and risk scores of cesarean delivery due to cephalopelvic disproportion at Kumpawapi Hospital - ศักดิ์สง่าวงษ์, สมบัติ (Journal of Medicine and Health Sciences, 2018)
One hundred singleton, viable, term pregnant women with cephalic presentation who delivered by cesarean delivery due to cephalopelvic disproportion (CPD) and 200 pregnant women who delivered normally at Kumpawapi hospital during August 25, 2014 to May 18, 2016 were studied. Demographic data, obstetric characteristics, neonatal outcomes were collected from medical records. The anticipated risk indicators were compared between the control and CPD groups using the Student’s t test and Chi-square test. Univariate and multivariate regression analyses were used to assess significant risk factors and build a model predicting the risk of cesarean delivery due to CPD. From the model, a risk-scoring scheme was developed and evaluated using Receiver operating characteristic (ROC) and likelihood ratios (LR). Results found that five significant predictors for cesarean delivery due to CPD were identified: maternal height < 150 cm. (OR = 9.52, 95% CI = 2.29-39.50), nulliparity (OR = 3.78, 95% CI = 1.21-11.86), total pregnancy weight gain ≥ 15 kg (OR = 5.03, 95% CI = 1.65-15.38), fundal height ≥ 35 cm. (OR = 80.77, 95% CI = 25.01-260.81), birth weight ≥ 3,500 g. (OR = 9.78, 95% CI = 3.33-28.69). Conclusion that Risk scoring scheme was developed from these five predictors with the total score ranging from 0 - 8.5. A cut off point risk score was 2.5 used to classify pregnant women into low risk and high risk for CPD.